ОБ ОБРАТНОМ ВЛИЯНИИ КОСМИЧЕСКИХ ЛУЧЕЙ НА СВОЙСТВА ТУРБУЛЕНТНОСТИ И СТРУКТУРУ ДЖЕТОВ В РАДИОГАЛАКТИКАХ - Цвык, Н. А. (Одеські астрономічні публікації, 2011)
There are investigated how the electron (e) and proton (p) cosmic rays (CRs) influent on the formation of cosmic shock fronts and on the jet-cocoon structure in the radio galaxies (RGs). The matter parameters in the hot spot (HS) aria of RG jet head (on example of Cygnus A) are estimated. The HS-turbulence properties are studied, supporting that the RG morphological structure arises due to the collision-less shocks and the non-linear diffusive shock acceleration of CRs. There makes up a picture of matter transport in HS, accounting the influence of CRs on the shock evolution. It is shown, that the case of when the post-jet flow mirroring elastically from HS as with FRII RGs, responds to the Alfven and HD-vortex turbulence, that its energy transmits (by means of CRs) to the large-scale vortex turbulence. In the other case, when the magneto-sound turbulence is pumping with low number of CRs or with e-CRs that cooling down by synchrotron radiation, the post-jet flow makes up shocks easily, or this flow decelerates as with FRI RGs. The diffusive shock acceleration model predicts deficit of low-energy e-CRs at the shock front surface, and this will allow us to discover shocks by low-frequency radio observations.